Morpholine‐based RAFT agents for the reversible deactivation radical polymerization of vinyl acetate and N‐vinylimidazole. Issue 9 (28th May 2020) - Vijayakrishna, Kari; Manojkumar, Kasina; Haribabu, PM; GyanaRanjan, Behera; Tilottama, Baisakhi; Agirre, Amaia; Meabe, Leire; Mantione, Daniele; Porcarelli, Luca; R Leiza, Jose; Mecerreyes, David
Abstract: Reversible addition–fragmentation chain transfer (RAFT) polymerization of less‐activated monomers in a controlled fashion is challenging due to the high reactivity and instability of the propagating radicals. We have designed dithiocarbamate‐based RAFT agents with morpholine as activating 'Z' group and benzyl, ethyl(1‐ethanoate)yl, ethyl(2‐propanoate)yl and cyanomethyl as 'R' leaving groups and investigated them for the reversible deactivation radical polymerization of vinyl acetate (VAc) and N ‐vinylimidazole ( N ‐VIm). RAFT polymerization of VAc and N ‐VIm at 70 °C using azobisisobutyronitrile as a free radical initiator proceeded in a controlled fashion as demonstrated by a linear increase in molar mass with conversion. Interestingly, the polymerization of VAc followed fast kinetics (approx. 60 min) with good to moderate control affording high‐molar‐mass poly(VAc) polymers. Furthermore, the synthesized chain transfer agents were able to polymerize N ‐VIm under controlled conditions. The morpholine RAFT agents bearing cyanomethyl and ethyl(2‐propanoate)yl leaving groups showed better control of the polymerization of VAc and N ‐VIm compared to the others. © 2020 Society of Chemical Industry Abstract : RAFT polymerization of N ‐vinylimidazole followed pseudo‐first‐order kinetics. Morpholine‐based chain transfer agents for rapid polymerization of vinyl acetate afforded high‐molar‐mass poly(vinyl acetate) (up to 130 kg mol −1 ).